Women's active role in climate change mitigation and adaptation in Latin America - Sarruf Romero, Lauren P.; Moreno, Carlos David (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
How have climate-smart agriculture (CSA) interventions improved gender issues in rural communities belonging to Climate-Smart Villages (CSV) in Colombia, Guatemala, and Honduras?